Optimism of characters in Andrea Hirata's Novel Entitled “Orang-Orang Biasa”: An Overview of Literature Psychology - Afendi, Petrus (Indonesian Values and Character Education Journal, 2021)
Optimism is an attitude or pattern of positive thinking towards a problem or problem with strong self-defense so that self-confidence grows. This optimistic mindset tends to be less owned by someone for several reasons: lack of human resources, which makes a person not confident in making a decision. This study describes the aspects and functions of the character's optimism in Andrea Hirata's Orang-Orang Biasa novel. The approach used in this analysis uses literature psychology theory, which focuses on the optimism aspect proposed by Goleman. The type of research used is qualitative research with the data source is the novel Orang-Ordinary by Andrea Hirata. The data collection method used a documentation study, namely by reading extensively and repeatedly to get the content by the desired study. The analysis technique is by reducing the data or selecting the data, presenting the data in quotations, and drawing conclusions as the final stage of the research. Based on the results of the study, it shows that the optimism aspect in Andrea Hirata's Orang-Orang Biasa novel is shown in various values, namely (1) having high expectations, (2) not being easily discouraged, (3) being able to motivate oneself, high self-confidence and ( 4) not being resigned while the function of optimism in the novel is (1) as a means of motivation to strengthen oneself, (2) as part of a form of self-defense to overcome life's problems and (3) optimism as a support system.